“PENGARUH PENERBITAN SUKUK TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH DI INDONESIA” - Juliana Br. Silaen; Sri Rahayu; Syamsul Effendi (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2021)
The Effect of Sukuk Issuance on the Financial Performance of Islamic Banking in Indonesia by using the Return On Asset (ROA) ratio to measure the profit of a company from the return on assets and return on equity as measured by Return On Equity (ROE). This study uses a linear regression analysis method where the dependent variables are ROA and ROE, and the independent variable is the issuance of sukuk. The results show that the issuance of sukuk does not have a significant effect on the Return On Assets (ROA) of Islamic commercial banks registered with the OJK. but the issuance of sukuk has a significant effect on the company's Return On Equity (ROE). Islamic general banking that is registered with the Financial Services Authority”.